BIM methodology implementation in structural design: Adaptation of procedures and information management - Gonçalo Ferreira Azevedo (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2022)
Building Information Modelling (BIM) is a methodology that accompanies technological evolution and consists of a set of processes and tools that allows the creation of a three-dimensional digital model. This model centralizes information, facilitating its access and exchange between the entities along the life cycle of a building. This study focuses on the application of BIM methodology within the framework of a structural design, identifying the benefits and limitations that it provides and indicating strategies that may be used to improve the quality of a project. A structural model was created through BIM-based platforms and then transferred to the calculation software where the structural analysis and design were carried out. After this, through the conceived digital model, various applications that it allows were explored, namely, the method of coordination and collaboration, detection of conflicts, production of drawings, the budget, and an immediate evaluation of the environmental impact of the structure This study demonstrates a significant improvement in the quality of the structural design. Therefore, even though some limitations still exist, the implementation of this methodology is essential to improve the process in the AEC sector.